2020
DOI: 10.1111/sji.12889
|View full text |Cite
|
Sign up to set email alerts
|

Antibody combinations for optimized staining of macrophages in human lung tumours

Abstract: The analysis of tumour‐associated macrophages (TAMs) has a high potential to predict cancer recurrence and response to immunotherapy. However, the heterogeneity of TAMs poses a challenge for quantitative and qualitative measurements. Here, we critically evaluated by immunohistochemistry and flow cytometry two commonly used pan‐macrophage markers (CD14 and CD68) as well as some suggested markers for tumour‐promoting M2 macrophages (CD163, CD204, CD206 and CD209) in human non–small cell lung cancer (NSCLC). Tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 71 publications
(191 reference statements)
0
10
0
Order By: Relevance
“…We also observed 2.81% (± 2.91) of monocytes in lung organoids compared to 0.76% (± 0.4) in the blood, suggesting a preferential accumulation of circulating monocytes in the human lung tissue. It has been reported that CD68 (KP-1) not only stains alveolar macrophages, but also neutrophils [ 47 ]. However, morphological examination of cell types in H&E-stained lung organoids revealed the presence of few neutrophils, which increased only slightly in the presence of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed 2.81% (± 2.91) of monocytes in lung organoids compared to 0.76% (± 0.4) in the blood, suggesting a preferential accumulation of circulating monocytes in the human lung tissue. It has been reported that CD68 (KP-1) not only stains alveolar macrophages, but also neutrophils [ 47 ]. However, morphological examination of cell types in H&E-stained lung organoids revealed the presence of few neutrophils, which increased only slightly in the presence of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Further, CD68 and CD163 antibodies must be chosen with caution as different antibodies influence the staining significantly. For instance, anti-CD68 antibody KP-1 stains both macrophages and neutrophils in human non–small cell lung cancer tissue, while anti-CD68 antibody PG-M1 does not [ 296 ]. In addition, some anti-CD163 antibodies are dependent on epitope accessibility and extracellular calcium which results in discrepancies among reported levels of CD163.…”
Section: The Cd163 + Macrophagesmentioning
confidence: 99%
“…It has been reported that both CD15 and CD68 are immunosuppressive markers that play an important role in suppressing T-cell-mediated immunity (46,47). CD68 is a major biomarker for the quantification of tumor-associated macrophages (TAMs) (48). As we all know, TAMs are a wellrecognized core element of tumor microenvironment (TME) and generally characterized as M2-like macrophages which are associated with tumor progression and poor prognosis (49,50).…”
Section: Discussionmentioning
confidence: 99%